2007
DOI: 10.1124/jpet.107.121707
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Course for Up- and Down-Regulation of the Cortical 5-Hydroxytryptamine (5-HT)2A Receptor Density Predicts 5-HT2A Receptor-Mediated Behavior in the Rabbit

Abstract: 5-Hydroxytryptamine (serotonin; 5-HT) 2 receptor agonists such as (Ϯ)-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI) injected systemically or directly into frontal cortex, elicit stereotyped head movements that are mediated by 5-HT 2A receptors. Chronic administration of 5-HT 2A receptor antagonists can produce either a down-regulation, e.g., d-2-bromolysergic acid diethylamide (BOL) or an up-regulation, e.g., ␣-phenyl-10(2-phenylethyl)-4-piperidinemethanol (MDL11,939) of cortical 5-HT 2A receptors in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In another study, Dave et al (2007) were able to relate the production of head bobs to 5-HT 2A receptor density in the cortex. DOI was infused bilaterally into the mPFC.…”
Section: Rabbit Modelsmentioning
confidence: 99%
“…In another study, Dave et al (2007) were able to relate the production of head bobs to 5-HT 2A receptor density in the cortex. DOI was infused bilaterally into the mPFC.…”
Section: Rabbit Modelsmentioning
confidence: 99%
“…The affinity for these receptors (Kd) was not altered (Aloyo et al 2001). In addition, it has been shown that downregulation of the 5-HT 2A receptor is associated with decreases in the ability of DOI to elicit head bobs (Aloyo et al 2001;Dave et al 2007). Similarly, upregulation of the 5-HT 2A receptor with no change in the density of the 5-HT 2C receptor resulted in an enhancement of trace eyeblink conditioning (Harvey et al 2004).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, these studies established the rabbit eyeblink model as a tool for monitoring inverse agonism at a systems level. Further studies by the Harvey group characterized the effects of chronic inverse agonist treatment on 5-HT 2A receptor density [47, 48]. When rabbits were repeatedly administered the inverse agonists MDL11939 and M100, 907, there was a resultant increase in 5-HT 2A receptor expression as measured by radioligand binding [47, 48].…”
Section: -Ht2 Receptor Constitutive Activity and Inverse Agonismmentioning
confidence: 99%
“…Further studies by the Harvey group characterized the effects of chronic inverse agonist treatment on 5-HT 2A receptor density [47, 48]. When rabbits were repeatedly administered the inverse agonists MDL11939 and M100, 907, there was a resultant increase in 5-HT 2A receptor expression as measured by radioligand binding [47, 48]. Moreover, there were corresponding behavioral effects as a consequence of the receptor up-regulation.…”
Section: -Ht2 Receptor Constitutive Activity and Inverse Agonismmentioning
confidence: 99%